(untitled) (Olhar de Professor, 2024)
The main objective of this article is to understand the challenges faced by legal instruments in restructuring High School education. For this analysis, the Common National Curriculum Base, the Provisional Measure No. 746/2016 converted into the Law that implemented the New High School Education (Law 13.415/2017), as well as the Bill No. 5.230/2023, will be considered. The research addresses the process of formulating legislation, focusing on Educational Policies, highlighting the underlying interests in certain historical periods. The scope of this study seeks to promote reflections on the choices and strategies of educational reform, aiming to understand the complexity of its implementation in everyday school life. Therefore, it aims to identify the challenges between the theoretical field of the norm and its practical application, highlighting issues related to effectiveness in the educational context.